Cultish ebook The language of fanaticism. - Montell, Amanda (2021)
"One of those life-changing reads that makes you see—or, in this case, hear—the whole world differently." —Megan Angelo, author of Followers "At times chilling, often funny, and always perceptive and cogent, Cultish is a bracing reminder that the scariest thing about cults is that you don't realize you're in one till it's too late."—Refinery29.com The New York Times bestselling author of The Age of Magical Overthinking and Wordslut analyzes the social science of cult influence: how "cultish" groups, from Jonestown and Scientologists to SoulCycle and social media gurus, use language as the ultimate form of power. What makes "cults" so intriguing and frightening? What makes them powerful? The reason why so many of us binge Manson documentaries by the dozen and fall down rabbit holes researching suburban moms gone QAnon is because we're looking for a satisfying explanation for what causes people to join—and more importantly, stay in—extreme groups. We secretly want to know: could it happen to me? Amanda Montell's argument is that, on some level, it already has . . . Our culture tends to provide pretty flimsy answers to questions of cult influence, mostly having to do with vague talk of "brainwashing." But the true answer has nothing to do with freaky mind-control wizardry or Kool-Aid. In Cultish, Montell argues that the key to manufacturing intense ideology, community, and us/them attitudes all comes down to language. In both positive ways and shadowy ones, cultish language is something we hear—and are influenced by—every single day. Through juicy storytelling and cutting original research, Montell exposes the verbal elements that make a wide spectrum of communities "cultish," revealing how they affect followers of groups as notorious as Heaven's Gate, but also how they pervade our modern start-ups, Peloton leaderboards, and Instagram feeds. Incisive and darkly funny, this enrapturing take on the curious social science of power and belief will make you hear the fanatical language of "cultish" everywhere.